The value of human community: Solovjov and Teilhard de Chardin as the inspiring challenges of modernity - Plašienková, Zlatica (Folia Philosophica, 2005)
The process of European integration is characterized by various challenges of modernity. Many of them compel us to reflect on the issue of uniting or even on the value of human being. The author found inspiration for these considerations in two conceptions. First of them claims that the process of creating unity (on every individual and social level) includes an experience of ambivalence. The second one pivots on the idea that the process of creating unity on every social level (communities) is determinedby the parallel process on the individual level that is on the level of individual lives (personal, internal) of people comprising a given community. The author of this article based her considerations on the inspiring spiritual heritage of V. Solovjov and Teilhard de Chardin, in the first place on their reflection on the principle of unity and love, which concerns the issue of human unity creation.